Facebook communities about nostalgic photos of Turkey: creative practices of remembering and representing the past. Issue 1 (2nd January 2017) - Savaş, Özlem
ABSTRACT: This article focuses on Facebook communities about nostalgic photos of Turkey to explore how citizenship is enacted through the participatory and collaborative use of social media to remember and represent the past. By sharing their personal photos, knowledge, testimonies, narratives and life stories, members of these communities actively and creatively use social media to generate new ways of remembering and representing the past, as well as improving its accessibility and visibility. Furthermore, through exchanging affectively and politically charged photos and conversations about the past, participants fashion nostalgia as a public feeling that becomes a source for affective political criticism of the present. This article addresses the participatory and collaborative creation of knowledge and memory of the past to discuss everyday creative citizenship practices facilitated by social media.